2011
DOI: 10.5222/jtaics.2011.292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dexmedetomidine versus Midazolam/Remifentanil Combination for Monitorized Anaesthesia Care

Abstract: ÖZETAmaç: Monitörize anestezi bakımında deksmedetomidin ile midazolam/remifentanil kombinasyonunun nazal septum cerrahisinde karşılaştırılması amaçlandı.Gereç ve Yöntem: Lokal anestezi altında nazal septum cerrahisi planlanan 50 hasta rasgele iki gruba ayrıldı. Grup D'ye 10 dk. Sonuç: Monitorize anestezi bakımında hızlı sedasyon istendiğinde, akciğer hastalığı yoksa desaturasyon açısından uygun önlemler alınarak midazolam/remifentanil kombinasyonu; semptomatik akciğer hastalığı olanlarda maliyeti göz önünde bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…These cardiovascular side effects can be reduced to a negligible level by lowering the initial loading dose. When infusion is discontinued, these levels increase slowly, and no rebound cardiovascular effects and symptoms of withdrawal syndrome are observed [17]. In the present study, we found that systolic and diastolic arterial pressures in the dexmedetomidine group that received infusion at a rate of 0.2 μg kg −1  h −1 were significantly lower than those in the control group ( p  < 0.05).…”
Section: Discussionsupporting
confidence: 46%
“…These cardiovascular side effects can be reduced to a negligible level by lowering the initial loading dose. When infusion is discontinued, these levels increase slowly, and no rebound cardiovascular effects and symptoms of withdrawal syndrome are observed [17]. In the present study, we found that systolic and diastolic arterial pressures in the dexmedetomidine group that received infusion at a rate of 0.2 μg kg −1  h −1 were significantly lower than those in the control group ( p  < 0.05).…”
Section: Discussionsupporting
confidence: 46%